Det demokratiske argument for absolut ytringsfrihed - Lægaard, Sune (Politik, 2014)
The article considers the claim that absolute freedom of speech is a necessary precondition for democratic legitimacy based on a reconstruction of an argument o ered by Ronald Dworkin. e question is why free speech should be a precondition for democratic legitimacy and why it should be so extensive that hate speech laws limiting free speech should be rejected? e article accounts for the concepts of legitimacy and democracy, analyses the legitimacy argument for free speech, and discusses a number of problems with it.